Nowe technologie ICT w polskich przedsiębiorstwach na tle Unii Europejskiej - Mundry, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Information and communication technologies more and more into the lives of enterprises. They affect both the improvement of production processes and the same product. Companies can also extend its reach and increase the speed of response to changing customer needs. ICT can also adjust flexibly to changing economic realities.ICT technology is still new and not all consumers have access to it. It is also associated with large capital expenditure. Poland on the background of ICT in a EU countries falls significantly below the average. By Polish companies to fully compete with more developed businesses, we need more and more integration of ICT.
Keywords: Polska; Unia Europejska; nowe technologie; polskie przedsiębiorstwa